Increased Inflammation and Unchanged Density of Synaptic Vesicle Glycoprotein 2A (SV2A) in the Postmortem Frontal Cortex of Alzheimer’s Disease Patients - Metaxas, Athanasios; Thygesen, Camilla; Briting, Sanne R. R.; Landau, Anne M.; Darvesh, Sultan; Finsen, Bente (Frontiers in Cellular Neuroscience, 2019)
Sections from the middle frontal gyrus (Brodmann area 46) of autopsy-confirmed Alzheimer’s disease (AD) patients and non-demented subjects were examined for the prevalence of hallmark AD pathology, including amyloid-β (Aβ) plaques, phosphorylated tau (pTau) tangles, neuroinflammation and synaptic loss (n=7 subjects/group). Dense-core deposits of Aβ were present in all AD patients (7/7) and some non-demented subjects (3/7), as evidenced by 6E10 immunohistochemistry. Levels of Aβ immunoreactivity were higher in AD vs. non-AD cases. For pTau, AT8-positive neurofibrillary tangles and threads were exclusively observed in AD patient tissue. Levels of [3H]PK11195 binding to the translocator protein (TSPO), a marker of inflammatory processes, were elevated in the grey matter of AD patients compared to non-demented subjects. Levels of [3H]UCB-J binding to synaptic vesicle glycoprotein 2A (SV2A), a marker of synaptic density, were not different between groups. In AD patients, pTau immunoreactivity was positively correlated with [3H]PK11195, and negatively correlated with [3H]UCB-J binding levels. No correlation was observed between Aβ immunoreactivity and markers of neuroinflammation or synaptic density. These data demonstrate a close interplay between tau pathology, inflammation and SV2A density in AD, and provide useful information on the ability of neuroimaging biomarkers to diagnose AD dementia.